Perception of primary education teachers on the development of research skills in nature science classes - Marieta NEAGU; Viorel BOCANCEA (Acta et Commentationes, Sciences of Education, 2023)
The article presents essential aspects of the influence of teachers' perception on the development of investigative skills of young school-aged students in the context of radical changes in society and also in the education system. The results of this research are presented regarding the identification of teachers' opinions, perceptions, attitudes and motivations concerning the choice of teaching strategies and their use in the development of investigative skills in primary education students, within the teaching of the Natural Sciences discipline, taking into account the influence of autonomous components of the development of the young schoolchild.